The SGLT2 inhibitor ertugliflozin causes a switch of cardiac substrate utilization leading to reduced cardiac mTOR-signaling, unfolded protein response and apoptosis. (14th October 2021) - Moellmann, J; Mann, P; Krueger, K; Klinkhammer, B; Boor, P; Marx, N; Lehrke, M
Abstract: Introduction: SGLT2 inhibitors reduce hospitalization for heart failure in patients with and without diabetes. The underlying mechanisms remain incompletely understood but might relate to the induction of a fasting like response with low blood glucose and insulin levels and increased ketone bodies. The study aimed to investigate underlying signaling pathways. Methods and results: Cardiac hypertrophy was induced by transverse aortic constriction (TAC) surgery in 20-week-old C57Bl/6J mice. Mice were treated with the SGLT2 inhibitor ertugliflozin (225 mg/kg chow diet) or vehicle for a period of 10 weeks. Ertugliflozin significantly improved left ventricular systolic and diastolic function (dp/dtmax: TAC ctrl.: 8900±3362 mmHg/s vs. TAC ertu.: 12051±1604 mmHg/s (p<0.001) and dp/dtmin: TAC ctrl.: −7653±2770 mmHg/s vs. TAC ertu.: −10199±2463 mmHg/s (p<0.01); by millar catheter with dobutamine stress) and reduced myocardial fibrosis (p=0.17) and hypertrophy (p=0.09). This was paralleled by the expected fasting like response with lower glucose and insulin levels (HOMA-IR p<0.05) and increased ketone body concentrations (p<0.05). As a consequence cardiac insulin signaling (AKT-phosphorylation at Thr(308), 0.39-fold (p<0.01)) was reduced by ertugliflozin with less insulin-dependent glucose transporter GLUT4 expression (0.64-fold (p<0.05)) while fatty acid transporter CD36 (2.12-fold (p<0.001)) and the ketone body catabolizing key enzyme beta-hydroxybutyrate dehydrogenase BDH-1 were increased (1.59-fold (p<0.01)) in addition to AMPK-signaling (AMPK-phosphorylation at Thr(172), 1.62-fold (p<0.01)). This led to downstream inhibition of the mTOR pathway with reduced phosphorylation of p70S6K, 4E-BP1 and ULK1 (p70S6K-phosphorylation at Thr(389) (0.57-fold (p<0.05)), 4E-BP1-phosphorylation at Ser(65) (0.74-fold (p<0.05)) and ULK1-phosphorylation at Ser(757) (0.56-fold (p<0.01))). MTOR signaling critically mediates cardiac hypertrophy, endoplasmic reticulum stress, unfolded protein response (UPR) and adverse cardiac remodeling. Consistently, we found ertugliflozin to reduce ATF6 (0.69-fold (p<0.05)) and elf2α-phosphorylation at Ser(51) (0.66-fold (p=0.0611)) as well as downstream signaling (ATF4 0.58-fold (p<0.01); CHOP 0.36-fold (p<0.001)). This let to reduced caspase 3 (0.74-fold (p<0.05)), collagen I (0.60-fold (p<0.01)) and IL-1β (0.46-fold (p<0.01)) expression indicating less apoptosis, fibrosis and left ventricular remodeling with consequential reduction of BNP expression (0.60-fold (p<0.001)) in response to SGLT2 inhibition. Conclusion: The SGLT2 inhibitor ertugliflozin improves left ventricular function in a murine model of cardiac hypertrophy. Mechanistically, this was associated with a metabolic switch of cardiac substrate utilization with reduced cardiac insulin- and increased cardiac AMPK-signaling leading to reduced cardiac mTOR-signaling, unfolded protein response and apoptosis. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): MSD